The Evolution of Work-Life Balance: Redefining Priorities in Human Resource Management - Ferdy Leuhery; Sari Zulfiana Hasan; Vera Herlina Mustari; Raden Rara Ayu Widaningsih; Fatimah Malini Lubis (Dinasti Publisher, 2024)
The concept of work-life balance has undergone significant evolution in recent decades, reflecting shifting priorities and values in human resource management practices. This literature review explores the dynamic nature of work-life balance and its redefinition within contemporary organizational contexts. Drawing on scholarly works published from 2019 onwards, the review synthesizes key themes and trends surrounding work-life balance, encompassing factors such as technology integration, flexible work arrangements, and organizational culture. The analysis highlights the increasing emphasis placed on employee well-being and satisfaction, as organizations recognize the integral role of work-life balance in enhancing productivity and fostering a positive workplace environment. Moreover, the review examines the challenges and opportunities associated with achieving work-life balance amidst evolving societal norms and economic landscapes. By elucidating current perspectives and empirical findings, this paper contributes to a nuanced understanding of work-life balance dynamics and informs strategic approaches to human resource management in contemporary organizations.